Financial planning & analysis and performance management - Alexander, Jack, 1956- (Hoboken, New Jersey : Wiley, 2018)
"This book is the essential desk reference for CFOs, FP&A professionals, investment banking professionals, and equity research analysts. With thought-provoking discussion and refreshing perspective, this book provides insightful reference for critical areas that directly impact an organization's effectiveness. From budgeting and forecasting, analysis, and performance management, to financial communication, metrics, and benchmarking, these insights delve into the cornerstones of business and value drivers. Dashboards, graphs, and other visual aids illustrate complex concepts and provide reference at a glance, while the author's experience as a CFO, educator, and general manager leads to comprehensive and practical analytical techniques for real world application"--
Fundamentals of finance -- Key analytical tools and concepts -- Developing predictive and analytical models -- Building analytical capability -- Presenting and communicating financial information -- Business performance management -- Dashboards and key performance indicators -- Institutionalizing performance management -- Measuring and driving what¿s important : innovation, agility, and human capital -- The external view : benchmarking performance and competitive analysis -- Business projections and plans : introduction and best practices -- Budgets, operating plans, and forecasts -- Long-term projections -- Revenue and gross margins -- Operating expenses and effectiveness -- Capital management and cash flow : working capital -- Capital management and cash flow : capital assets -- Risk, uncertainty, and the cost of capital -- Capital investment decisions : introduction and key concepts -- Capital investment decisions : advanced topics -- Business valuation and value drivers -- Analysis of mergers and acquisitions -- Summary and where to from here?.
Includes index.
Keywords: Business enterprises -- Finance -- Handbooks, manuals, etc; Corporations -- Finance -- Handbooks, manuals, etc; Investment banking -- Handbooks, manuals, etc; Handbooks and manuals